Influence of Temperatures and Thermodynamic Parameters on pKa Values for Some Acids and Basic Imines Derived 3-Acetyl and 4-Acetyl Pyridines - Azzouz, A.S.P.; Sulaiman, R.D. (Asian Journal of Chemistry, 2013)
The work is concerned with the influence of temperature on the values of ionization constants for some acids and basic imines in fixed 10 % ethanol in a mixture of ethanol and water. These imines are in a forms of syn or anti oxime and phenolic or amino Schiff bases, containing phenol and amine groups in ortho, meta and para positions on the aromatic rings of primary amine sides. The thermodynamic of ionization for imines confirm that ionization reactions in these imines are accompanied by an increase of parameters DGº and DHº. These mean that ionization reactions in these imines are non-spontaneous and endothermic respectively. DSº values of ionization reactions estimated have a negative signs.